Efektivitas Pola Komunikasi dalam Bimbingan PKL: Studi Kasus Interaksi Dosen-Mahasiswa di Universitas Imelda Medan - Angelia Putriana (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
The communication pattern between lecturers and students plays an important role in ensuring the effectiveness of the learning and mentoring process, especially in the context of Practical Field Work (PKL) supervision. This study employs a qualitative research method as an interpretive method, based on real phenomena occurring in the field. The findings of this study reveal that the communication patterns used include face-to-face meetings, communication technology, and feedback, with the barriers identified being time constraints, differences in expectations, and non-verbal communication. This research discusses the effectiveness of face-to-face meetings between lecturers and students, which is considered very important and requires more flexible and effective scheduling. Furthermore, the use of technology such as email and WhatsApp has proven effective in maintaining smooth communication, and constructive and detailed feedback from lecturers is highly appreciated by students. Finally, openness and empathy are needed by both lecturers and students to help reduce misunderstandings and improve the quality of guidance. Therefore, it is important for educational institutions to continuously develop and implement communication strategies that support an effective and efficient PKL supervision process.